Fetal alcohol spectrum disorders (FASD) – What we know and what we should know – The knowledge of German health professionals and parents. (May 2018) - Landgraf, Mirjam N.; Albers, Lucia; Rahmsdorf, Birte; Vill, Katharina; Gerstl, Lucia; Lippert, Michaela; Heinen, Florian
Abstract: Objective: The objective of our study was to evaluate the knowledge about fetal alcohol spectrum disorders (FASD) and the implementation of the German guideline for FASD among different professionals in the health and social system and among parents with children with FASD. Methods: A questionnaire about FASD, containing 20 items, was sent by post to all children's hospitals (n = 287), all hospitals for child and adolescent psychiatry (n = 173), all social paediatric centres (n = 162), all neuropaediatricians (n = 129) and all youth welfare offices (n = 672) in Germany. Furthermore a link to the questionnaire as online version was put in the member's newsletter by 14 relevant professional societies. Besides, the questionnaire was distributed personally to the attendees of the annual national FASD conference (n = 363). Results: Altogether 428 persons took part in the survey. 273 participants were professionals and 155 parents of children with FASD. More than 95% of the professionals and parents knew that alcohol consumption during pregnancy constitutes a risk for the child. The prevalence of maternal alcohol consumption and of FASD was underestimated. Although approx. 70% of the professionals knew which disorders belong to FASD just a few could tell their specific deficits. Questions regarding effective intervention for children with FASD and the long-term outcome were only partially answered correctly. Discussion: Professionals in the German health and social system are aware of FASD but underestimate the level of damage and the impact on every day functioning of the affected people. Highlights: The German professionals and parents in this survey are aware of the potential harm of intrauterine alcohol exposure. However,  the responding professionals underestimate the prevalence of fetal alcohol spectrum disorders (FASD). The German guideline for FASD is used by ¾ of the interviewed paediatricians and child psychiatrists for diagnosis. Nevertheless many professionals have difficulties to distinguish the different spectrum disorders of FASD. The participating professionals underestimate the impact on everyday life and the prognosis of children with FASD.